Hard and Soft Border Paradigm for Border Governance in Indonesia: A General Review - Ulfa, Nadlirotul; Fimmastuti, Desiana Rizka; Nia Rahmah, Anisa Nur (Political Science Program, Universitas Negeri Semarang, 2018)
This study focuses on border governance paradigm for various relevant policies in Indonesia. By applying literature review method, it reveals that Indonesian border governance paradigm has shifted from hard to soft border paradigm. The change has significant impact on how managing border areas in the country. In fact, both paradigms have their own advantages and limitations. This study also shows that the preference between hard or soft boarder paradigm influences the decisions on how the government understand the complexity of the border.